Sistem Pemasaran Hasil Perikanan dan Pengentasan Kemiskinan Nelayan Desa Branta Pesisir Pamekasan - Rachman Hakim (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2021)
Abstract Branta Pesisir Village is one of the coastal areas in Pamekasan district. Branta Pesisir Village has high economic potential, but the poverty of fishermen still occurs amidst the abundance of marine resources. This research was conducted to find out about the marketing system of fishery products and its relation to poverty alleviation of fishermen in the Branta Pesisir Village using a qualitative descriptive approach. The results of the study show that the weather greatly influences the rise and fall of fish prices, due to changes in weather, fishermen cannot go to sea, resulting in fewer fish catches, so that fishermen's poverty still occurs and makes it difficult for fishermen to fulfill their daily lives. So far, the marketing system for fishery products is still very simple, fishermen do not have direct access to factories. Fish marketing through intermediaries such as agents, collectors, and baskets. They tend to be able to manipulate the price of fish to get more profit.